Review of Mode Selection Probability Public Transportation Route Lhokseumawe - Medan - Yunidar Lestari; Fasdarsyah; Herman Fithra; Burhanuddin; Nura Usrina; T Mudi Hafli; Meutia (Faculty of Engineering, Malikussaleh University, 2024)
In an intercity movement, the choice of mode plays a fairly important role, someone will move from one city to another will certainly consider many things. In traveling during the day or night on the Lhokseumawe Medan route or vice versa, travelers will be faced with a choice of land transportation modes, namely using the Putra Pelangi Bus and the Hiace Minibus. This study aims to determine the characteristics of mode users, factors that influence mode selection. Modeling analysis was carried out using multiple linear regression analysis method. Multiple linear analysis serves to measure the effect of the independent variables on the dependent variable.There are two regression models in this study, the first model based on the characteristics of the mode (Y1) and the second based on the characteristics of the passengers (Y2). The best model based on the characteristics of the mode is Y1= 0.656 + 0.021X1 + 0.108X2 + 0.019X3 + 0.130X4 with R2=0.962 and The best model based on the characteristics of the passengers is Y2= Y= 1,775-0,032X1+0,094X2-0,005X3+0,028X4+0,079X5+0,059X6-0,226X8 with R2=0.564. Keywords: Model; Multiple linear regression analysis; Ordinary Least Square (OLS)